Carbon Nanomaterials in Different Dimensions for Electrochemical Energy Storage. Issue 17 (29th March 2016) - Ni, Jiangfeng; Li, Yan
Abstract : Carbon nanomaterials including fullerenes, carbon nanotubes, graphene, and their assemblies represent a unique type of materials in diverse formats and dimensions. They feature a large surface area, superior conductivity, fast charge transport, and intrinsic stability, which are essentially required for various electrochemical energy storage (EES) systems such as Li‐ion batteries, supercapacitors, and redox flow cells. The scaled‐up and reliable production and assembly of carbon nanomaterials is a prerequisite for the development of carbon nanomaterial‐based EES devices. In this progress report, the preparation of carbon nanostructures and the state‐of‐the‐art applications of carbon nanomaterials with different dimensions in versatile EES systems are summarized. The importance of the synergetic effect induced by interactions between nanocarbons and active electrode species is highlighted. The main challenges and prospects in this field are also discussed. Abstract : Carbon nanomaterials including fullerenes, carbon nanotubes, graphene, and their assemblies represent a unique type of materials for electrochemical energy storage. In this progress report, state‐of‐the‐art applications of carbon nanomaterials with different dimensions in Li‐ion batteries, supercapacitors, and redox flow cells are described and discussed in detail, with the most recent and typical progresses being the focus.